Implementation of Image Segmentation Techniques to Detect MRI Glioma Tumour - Siti Rafidah Binti Kassim; Setyawan Widyartoh; Mohammad Syafrullah; Krisna Adiyarta; Widya Kumala Sari (IAES Indonesia Section, 2019)
Image identification to detect a tumour needs several stages of image processing along with identifying analysis. To get an accurate segmentation of the tumour contour and to identify brain tumour based on brain magnetic resonance imaging (MRI), a suitable techniques and stages of image processing are required to be applied. One technique of mid-level image processing became an objective this work. The objective of the study is to segment the boundary of tumour by applying the Modification of Region Fitting (MRF) method in term of data fitting. The performance of the Region Scalable Fitting (RSF) method and Modified Region Scalable Fitting (MRSF) is evaluated by comparing the number of iterations. As the result, the MRF method has successfully segmented the initial region of braintumour images.